Peningkatan Efisiensi dan Pemberdayaan Anggota Melalui Digitalisasi Manajemen Operasional KUBE Mutiara Berkah Abadi - Azzat, Noor Nailie; Mohammad, Gunawan; Susila, Agus Dwi (Journal of Appropriate Technology for Community Services, 2025)
This community service program aims to improve the operational efficiency of the KUBE Mutiara Berkah Abadi (Joint Business Group) in Krapyak Village, Jepara, through the digitalization of operational management and the design of ergonomic product display racks. The methods used include training, socialization, and mentoring for the implementation of digital technology as well as the design of product display racks. The results showed increased efficiency in transaction recording and inventory management, along with an increase in customer interest due to more attractive product arrangements. Through digitalized management, KUBE can monitor stock and sales in real-time, reducing the risk of lost sales due to insufficient stock or unsold products. This program contributes to empowering KUBE members by enhancing digital skills and product design.